Synthesis and Evaluation of the Acetylcholinesterase Inhibitory Activities of Some Flavonoids Derived from Naringenin - The-Huan Tran; Thi-Thu-Hien Vo; Thi-Quynh-Nhi Vo; Thi-Cam-Nhung Cao; Thai-Son Tran (The Scientific World Journal)
Alzheimer’s disease (AD) is an irreversible neurodegenerative disease that affects many older people adversely. AD has been putting a huge socioeconomic burden on the healthcare systems of many developed countries with aging populations. The need for new therapies that can halt or reverse the progression of the disease is now extremely great. A research approach in the finding new treatment for AD that has attracted much interest from scientists for a long time is the reestablishment of cholinergic transmission through inhibition of acetylcholinesterase (AChE). Naringenin is a flavonoid with the potential inhibitory activity against AChE. From naringenin, many other flavonoid derivatives, such as flavanones and chalcones, can be synthesized. In this study, by applying the Williamson method, nine flavonoid derivatives were synthesized, including four flavanones and five chalcones. The evaluation of AChE inhibitory activity by the Ellman method showed that there were four substances (2, 4, 5, and 7) with relatively good biological activities (IC50 < 100 μM), and these biological activities were better than that of naringenin. The molecular docking revealed that strong interactions with amino acid residue Ser200 of the catalytic triad and those of the peripheral region of the enzyme were crucial for strong effects against AChE. Compound 7 had the strongest AChE inhibitory activity (IC50 13.0 ± 1.9 μM). This substance could be used for further studies.